The last good guy [large type] - Parker, T. Jefferson (Thorndike Press large print core series., 2019)
When hired by a beautiful and enigmatic woman to find her missing younger sister, private investigator Roland Ford immediately senses that the case is not what it seems. He is swept up in a web of lies and secrets as he searches for the teenager, and even his new client cannot be trusted. His investigation leads him to a secretive charter school, skinheads, a cadre of American Nazis in a desert compound, an arch-conservative celebrity evangelist, and, finally, to the girl herself. Ford's most challenging case to date will leave him questioning everything he thought he knew about decency, honesty, and the battle between good and evil--if it doesn't kill him first.